Corticosteroid injections during the COVID-19 pandemic: experience from a UK centre. (1st September 2020) - McKean, David; Chung, Siok Li; Fairhead, Rory; Bannister, Oliver; Magliano, Malgorzata; Papanikitas, Joseph; Wong, Nick; Hughes, Richard
Abstract : Aims: To describe the incidence of adverse clinical outcomes related to COVID-19 infection following corticosteroid injections (CSI) during the COVID-19 pandemic. To describe the incidence of positive SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) testing, positive SARS-COV2 IgG antibody testing or positive imaging findings following CSI at our institution during the COVID-19 pandemic. Methods: A retrospective observational study was undertaken of consecutive patients who had CSI in our local hospitals between 1 February and 30June 2020. Electronic patient medical records (EPR) and radiology information system (RIS) database were reviewed. SARS-CoV-2 RT-PCR testing, SARS-COV2 IgG antibody testing, radiological investigations, patient management, and clinical outcomes were recorded. Lung findings were categorized according to the British Society of Thoracic Imaging (BSTI) guidelines. Reference was made to the incidence of lab-confirmed COVID-19 cases in our region. Results: Overall, 1, 656 lab-confirmed COVID-19 cases were identified in our upper tier local authority (UTLA), a rate of 306.6 per 100, 000, as of 30June 2020. A total of 504 CSI injections were performed on 443 patients between 1 February and 30June 2020. A total of 11 RT-PCR tests were performed on nine patients (2% of those who had CSI), all of which were negative for SARS-CoV-2 RNA, and five patients (1.1%) received an SARS-CoV-2 IgG antibody test, of which 2 (0.5%) were positive consistent with prior COVID-19 infection, however both patients were asymptomatic. Seven patients (1.6%) had radiological investigations for respiratory symptoms. One patient with indeterminate ground glass change was identified. Conclusion: The incidence of positive COVID-19 infection following corticosteroid injections was very low in our cohort and no adverse clinical outcomes related to COVID-19 infection following CSI were identified. Our findings are consistent with CSI likely being low risk during the COVID-19 pandemic. The results of this small observational study are supportive of the current multi-society guidelines regarding the judicious use of CSI. Cite this article: Bone Joint Open 2020;1-9:605–611.